Efficacy and Safety of Hybrid Comprehensive Telerehabilitation (HCTR) for Cardiac Rehabilitation in Patients with Cardiovascular Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zheming Yang; Xiaodong Jia; Jiayin Li; Zhu Mei; Lin Yang; Chenghui Yan; Yaling Han (Hindawi-Wiley, 2023)
Backgrounds. Cardiovascular disease (CVD) is a serious condition that poses threats to patients' quality of life and life expectancy. Cardiac rehabilitation is a crucial treatment option that can improve outcomes for CVD patients. Hybrid comprehensive telerehabilitation (HCTR) is a relatively new approach. In the context of pandemics, HCTR can minimize the risk of cluster infections by reducing hospital visits while delivering effective rehabilitation care. This study is aimed at assessing the efficacy and safety of HCTR as a secondary prevention measure for CVD patients compared to usual rehabilitation care. Methods. We searched PubMed, Embase, The Web of Science, The Cochrane Library, and PsychINFO for all related studies up to January 20, 2023. Two reviewers independently screened the titles and abstracts of potentially eligible articles based on the predefined search criteria. Data were analyzed using a comprehensive meta-analysis software (RevMan5.3). Results. Eight trials, involving 1578 participants, were included. HCTR and usual rehabilitation care provide similar effects on readmission rates (odds ratio OR=0.90 (95% CI 0.69-1.17), P=0.43) and mortality (odds ratio OR=1.06 (95% CI 0.72-1.57), P=0.76). Effects on Short Form-36 Health Status Questionnaire (SF-36) score were also similar (SMD: 1.32 (95% CI-0.48-3.11), P=0.15). Compared with usual rehabilitation care, HCTR can improve peak oxygen uptake (VO2 peak) (SMD: 0.99 (95% CI 0.23-1.74), P=0.01) and 6-minute walking test (6MWT) (SMD: 10.02 (95% CI 5.44-14.60), P<0.001) of patients. Conclusions. Our findings indicate that HCTR is as effective as traditional rehabilitation care in reducing readmission rates and mortality and improving quality of life in patients with CVD. However, HCTR offers the added advantage of improving VO2 peak and 6MWT, measurements of cardiorespiratory fitness and functional capacity, respectively. These results suggest that HCTR can be a safe and effective alternative to traditional rehabilitation care, offering numerous benefits for CVD patients. Clinical Study Registration Number. This trial is registered with NCT02523560 and NCT02796404.